Circular RNA ACTN4 promotes intrahepatic cholangiocarcinoma progression by recruiting YBX1 to initiate FZD7 transcription - Chen, Qinjunjie; Wang, Haibo; Li, Zheng; Li, Fengwei; Liang, Leilei; Zou, Yiran; Shen, Hao; Li, Jun; Xia, Yong; Cheng, Zhangjun; Yang, Tian; Wang, Kui; et al. (Journal of Hepatology, 2022)
Intrahepatic cholangiocarcinoma (ICC) is a primary liver cancer with high aggressiveness and extremely poor prognosis. The role of circular RNAs (circRNAs) in ICC carcinogenesis and progression remains to be determined. CircRNA microarray was performed to screen significantly upregulated circRNAs in paired ICC and non-tumor tissues. Colony formation, transwell, and xenograft models were used to examine the role of circRNAs in ICC proliferation and metastasis. RNA pulldown, mass spectrometry, chromatin immunoprecipitation, RNA-binding protein immunoprecipitation, chromatin isolation by RNA purification, electrophoretic mobility shift assay, and luciferase reporter assays were used to explore the molecular sponge role of the circRNA (via miRNA binding), and the interaction between circRNA and RNA-binding proteins. Hsa_circ_0050898, which originated from exon 1 to exon 20 of the ACTN4 gene (named circACTN4), was significantly upregulated in ICC. High circACTN4 expression was associated with enhanced tumor proliferation and metastasis in vitro and in vivo, as well as a worse prognosis following ICC resection. In addition, circACTN4 upregulated Yes-associated protein 1 (YAP1) expression by sponging miR-424-5p. More importantly, circACTN4 also recruited Y-box binding protein 1 (YBX1) to stimulate Frizzled-7 (FZD7) transcription. Furthermore, circACTN4 overexpression in ICC cells enhanced the interaction between YAP1 and β-catenin, which are the core components of the Hippo and Wnt signaling pathways, respectively. CircACTN4 was upregulated in ICC and promoted ICC proliferation and metastasis by acting as a molecular sponge of miR-424-5p, as well as by interacting with YBX1 to transcriptionally activate FZD7. These results suggest that circACTN4 is a potential prognostic marker and therapeutic target for ICC. Intrahepatic cholangiocarcinoma is a primary liver cancer associated with aggressiveness and extremely poor prognosis. It is essential for therapeutic development that we uncover relevant pathogenic pathways. Herein, we showed that a circular RNA (circACTN4) was highly expressed in intrahepatic cholangiocarcinoma and was positively associated with tumor growth and metastasis through key developmental signaling pathways. Thus, circACTN4 could be a prognostic biomarker and therapeutic target for intrahepatic cholangiocarcinoma. [Display omitted] •CircACTN4 was upregulated in ICC and is associated with a worse prognosis.•CircACTN4 promoted ICC growth and metastasis in vitro and in vivo.•CircACTN4 recruited YBX1 to initiate FZD7 transcription.•CircACTN4 acted as sponge of miR-424-5p to upregulate YAP1.•CircACTN4 enhanced the interaction between the Wnt/β-catenin and Hippo/YAP pathways.